2020
DOI: 10.1038/s41467-020-15132-z
|View full text |Cite
|
Sign up to set email alerts
|

Electrical monitoring of photoisomerization of block copolymers intercalated into graphene sheets

Abstract: Insulating polymers have received little attention in electronic applications. Here, we synthesize a photoresponsive, amphiphilic block copolymer (PEO-b-PVBO) and further control the chain growth of the block segment (PVBO) to obtain different degrees of polymerization (DPs). The benzylidene oxazolone moiety in PEO-b-PVBO facilitated chain-conformational changes due to photoisomerization under visible/ultraviolet (UV) light illumination. Intercalation of the photoresponsive but electrically insulating PEO-b-PV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…At least, WBC-derived ccfDNA potentially carries non-cancerous mutated DNA. Recent studies found that clonal hematopoiesis of indeterminate potential, (CHIP) can significantly contribute to the detection of false-positive mutations on genes like KRAS [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least, WBC-derived ccfDNA potentially carries non-cancerous mutated DNA. Recent studies found that clonal hematopoiesis of indeterminate potential, (CHIP) can significantly contribute to the detection of false-positive mutations on genes like KRAS [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the validation of ctDNA using UltraSEEK™ and ddPCR analyses, ccfDNA was extracted from 4 mL (MTP cohort) and 2 mL (GRO cohort) of the same cell-free plasma used for the diagnostic Cobas test and eluted in 100 µL (MTP cohort) and 52 µL (GRO cohort) of elution buffer using the QIAamp Circulating Nucleic Acid Kit (Qiagen, Hilden, Germany) according to the manufacturer’s recommendations as reported previously [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. CcfDNA yield was determined with either the LabChip ® GX Touch™ Nucleic Acid Analyzer (PerkinElmer, Waltham, MA, USA; MTP cohort) or the Qubit™ 1× dsDNA HS Assay Kit (Thermofisher Scientific, Waltham, MA, USA; GRO cohort).…”
Section: Methodsmentioning
confidence: 99%
“…The migration process is accelerated by the (i) difference in surface free energy between the molten polymer and precursor with a large carbon content, (ii) changes in temperature, and (iii) decomposition of the foaming agent. Although several studies based on the formation of carbonaceous char inhibiting the burning process of polymers have been conducted recently, there have been no clear results on the related fundamental properties and structural characteristics [ 37 , 101 , 102 , 103 , 104 ]. The widely used gas-phase process involves inert gas dilution and chemical quenching (scavenging) of active radicals.…”
Section: Types Of Flame Retardantsmentioning
confidence: 99%
“…Graphene and graphene oxide (GO) have exhibited promising flame-retardant performances. This is because they have a high thermal stability, strong barrier effect, and large specific surface adsorption capability, which are favorable for reducing heat and mass transfer [ 101 , 184 ]. Many studies have proven that graphene and its derivatives can have significant effects on the pyrolysis of polymers [ 36 , 98 , 99 , 185 ], as well as on their thermal conductivity, heat absorption, and dripping [ 184 , 185 , 186 , 187 ].…”
Section: Nanoparticles As Flame-retardant Fillersmentioning
confidence: 99%
“…Recently, amphiphilic block copolymers were intercalated into stacked graphene sheets in an aqueous solution. Importantly, the physical intercalation of the photoresponsive but electrically insulating block copolymers into the confined space between graphene sheets enabled electrical monitoring of conformational changes in the block copolymer at the molecular level . The electrical response at the microampere level was sensitive to visible/UV light, which was also proportional to the degree of polymerization of the photosensitive block.…”
Section: Exfoliation Approachesmentioning
confidence: 99%